Investigating a strategy for quantifying schistosome infection levels in preschool-aged children using prevalence data from school-aged children - Rivka M. Lim; Mark E. J. Woolhouse; Takafira Mduluza; Margo Chase-Topping; Derick N. M. Osakunor; Lester Chitsulo; Francisca Mutapi; Uwem Friday Ekpo (Public Library of Science (PLoS), 2020)
In 2012, the World Health Organisation (WHO) set out a roadmap for eliminating schistosomiasis as a public health problem by 2025. To achieve this target, preschool-aged children (PSAC; aged 6 years and below) will need to be included in schistosomiasis treatment programmes. As the global community discusses the tools and approaches for treating this group, one of the main questions that remains unanswered is how to quantify infection in this age group to inform treatment strategies. The aim of this study was thus to determine whether a relationship exists between levels of schistosome infection in PSAC and school-aged children (SAC), that can be used to determine unknown schistosome infection prevalence levels in PSAC. A systematic search of publications reporting schistosomiasis prevalence in African PSAC and SAC was conducted. The search strategy was formulated using the PRISMA guidelines and SPIDER search strategy tool. The published data was subjected to regression analysis to determine if a relationship exists between infection levels in PSAC and SAC. The interaction between SAC and community treatment history was also entered in the regression model to determine if treatment history significantly affected the relationship between PSAC and SAC prevalence. The results showed that a significant positive relationship exists between infection prevalence levels in PSAC and SAC for Schistosoma mansoni (r = 0.812, df (88, 1), p = <0.0001) and S. haematobium (r = 0.786, df (53, 1), p = <0.0001). The relationship was still significant after allowing for diagnostic method, treatment history, and the African sub-region where the study was conducted (S. mansoni: F = 25.63, df (88, 9), p = <0.0001; S. haematobium: F = 10.20, df (53, 10), p = <0.0001). Using the regression equation for PSAC and SAC prevalence, over 90% of the PSAC prevalence studies were placed in the correct WHO classifications category based on the SAC levels, regardless of treatment history. The study indicated that schistosome prevalence ...